A CORRELATIONAL STUDY OF WORK STRESS AND JOB PERFORMANCE AMONG BANK EMPLOYEES IN ILORIN METROPOLIS - Lasisi, Adekola Kamil; Annor, Patricia Omioguele (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
This study examined the relationship between work stress and job performance in the banking sector, within Ilorin Metropolis, Kwara State. The research method used was a descriptive survey of correlation type. The target population for this study consisted of all bank employees in Ilorin metropolis, Kwara State. A sample of 120 bank employees was randomly selected for the study. Data collection was done using a questionnaire called the "Work Stress and Job Performance Questionnaire" (WSJPQ). This is a self-constructed but well-validated instrument (r = 0.78 & 0.72). Data collected were analysed using percentage, mean and Pearson’s Product Moment Correlation statistical tool. The study uncovered that the level of work stress among the sample bank employees is moderate and the level of job performance among the respondents is high. It was also observed that there was a significant negative relationship between work stress and job performance of the sampled bank employees in Ilorin Metropolis, Kwara State. The study recommended that the banking sector should increase the quality of their services to reduce pressure from customers on the employees. Management should explore the possibility of implementing flexible work arrangements, such as flexible hours or remote work, to give employees more control over their work schedules and reduce the pressure.